Reliable transmission mechanism with differentiated protection in virtualized fiber-wireless access network - Ruyan WANG; Yishuang GAO; Xiao CHEN (Tongxin xuebao)
In view of the different reliability requirements of network service,a reliable transmission mechanism with differentiated protection was proposed in virtualized fiber-wireless access network.The quality of protection required by users and the fees that can be paid were used as a prerequisite.The backup protection resources were flexibly allocated by quantifying the multi-level protection quality with the probability of recovery.Then,for reducing traffic congestion and the unprotected services,the level service differentiation algorithm was used to choose protection link which was satisfied with the level of protection quality.The results show the proposed mechanism has more advantages in terms of long-term benefit-to-cost ratio and underlying network resource overhead,and provides users with a more flexible virtual network transmission while satisfying users’ reliability requirements.